Development of a stoichiometric magnesium potassium phosphate cement (MKPC) for the immobilization of powdered minerals. (April 2021) - De Campos, M.; Davy, C.A.; Djelal, N.; Rivenet, M.; Garcia, J.
Abstract: Ordinary Portland Cement (OPC)-based materials are not systematically adapted for immobilizing industrial hazardous waste, e.g. for aluminium powder or plutonium waste sludge. In such case, Magnesium Potassium Phosphate Cements (MKPC) represent an interesting alternative. The originality of this research is to develop a formulation of a MKPC paste for hazardous waste immobilization, which incorporates a maximum amount of such waste, preferably in powdered form. To this purpose, a stoichiometric MKPC paste is selected, and its properties are improved by powdered waste addition. Firstly, the physico-chemical mechanisms generating expansion in stoichiometric MKPC paste are analyzed. Swelling is attributed to a pH gradient in the paste, due to the progressive sedimentation of MgO particles in the fresh mix. Secondly, over-stoichiometric MgO is replaced by varying amounts of minerals simulating the waste, of different mineralogy and granulometry, in order to achieve sufficient workability and no swelling. An optimal formulation is proposed, which incorporates powdered fly ash at a fine-to-cement mass ratio (F/C) of 1. Its mechanical performance and endogenous dimensional changes are comparable to typical over-stoichiometric pastes, and they stabilize between 7 and 28 days.